Manajemen Risiko pada Pegawai Pabrik di Kabupaten Pemalang - Fadia Putri Dwi Dinanti; Amirah, Amirah (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study analyzes the Occupational Health and Safety (OHS) risk management in 50 workers of small-medium factories in Pemalang Regency using a descriptive quantitative approach with the HIRARC method and Likert scale questionnaires. The study focuses on 13 types of risks, both physical (machinery, chemicals, noise, ergonomics) and non-physical (psychosocial, wages, workload), based on respondents' perceptions. The results show that physical risks, such as machine accidents (38%), noise (40%), and fire (44%), are categorized as moderate-high but can be controlled through the use of personal protective equipment (56%), machine maintenance (52%), and training. The HIRARC matrix identifies four risks in the high category, particularly non-physical risks such as delayed wages (54%) and social pressure (44%). Administrative management is at a moderate level (40-52%), with major obstacles being heavy workload and poor ventilation. Recommendations include stress training, shift rotation, monthly monitoring of the HIRARC matrix, and improving Standard Operating Procedures (SOP) in accordance with Government Regulation No. 50/2012 to strengthen the OHS culture. This study contributes to local policies aimed at reducing accident incidents in rural industries.